A significant improvement of fine scheelite flotation through rheological control of flotation pulp by using garnet. (July 2019) - Chen, Wei; Chen, Fanfan; Bu, Xianzhong; Zhang, Guofan; Zhang, Chonghui; Song, Yonghui
Highlights: Garnet particles were added in the conditioning process in a fine scheelite ore flotation. The cleaning flotation process was significantly improved by the added coarse garnet. The pulp rheology of the cleaning flotation was changed by the garnet addition. There existed strong correlation between pulp rheology and flotation performance. Abstract: The paper proposes a novel method which utilizes the garnet to realize the rheological control of the flotation pulp in fine scheelite flotation. The garnet was added in the conditioning operation of the cleaning flotation stage. Sodium oleate and water glass were used as flotation collector and depressant, respectively. Flotation tests on the cleaning flotation with different addition of garnet were conducted, coupled with rheological measurements, flotation rate calculation and optical observations on the corresponding flotation pulp and froth. It is found that there exists strong correlation among the flotation rate, pulp rheology, froth and floc morphology in the cleaning flotation. As the garnet content in the cleaning flotation pulp increases, the viscosity of the flotation pulp decreases and the flotation rate increases; the floc morphology changes from big-branch type to globule-like and the flotation froth becomes cleaner. It is also found that the changes in the fluid properties of the flotation slurry caused by the garnet addition are closely related to the flotation selectivity. As the slurry yield stress decreases and the flotation slurry deviates nearer to the Bingham fluid, the flotation rate increases and the flotation selectivity improves. The results could potentially be used to improve the flotation performance of fine scheelite ore through rheological control of flotation pulp by garnet addition in cleaning flotation operations.